Perjalanan Hidup Abuya Muhtadi Banten - Nurcholis Azis; Wildan sahputra Siregar; Siti Maimunah Siregar; Siti Nurhasanah harahap; Wardah Nazhifah Hasibuan (AL-Ikhtiar : Jurnal Studi Islam, 2024)
This research discusses the life journey of Abuya Muhtadi Banten who is one of the charismatic kyai from Banten. The teachings about the Islamic teachings of Banten residents are very existent, this is based on oral history that has spread among the people of Indonesia. In addition, this paper was made to provide answers to people who deny the teachings of scholars who have been summarized and believed. This research aims to find out the life journey of Abuya Muhtadi Banten. This research is expected to answer questions about the life history of Abuya Muhtadi Banten. This research uses qualitative methods. With the results of the study, Abuya Muhtadi is the first child of Abuya Dimyathi who is also one of the successors and also the holder of the Raudhatul 'Ulum Islamic boarding school until now. Abuya Muhtadi since childhood has been taught and participated in following in his father's footsteps as a preacher, which began with the activities of studying and reciting the Koran conducted at boarding schools in Banten. Abuya Muhtadi's understanding of the Koran was used as a basis for exploring Islamic religious knowledge. Abuya Muhtadi is also one of the Mustayar PBNU administrators. Abuya Muhtadi is one of the scholars who has a commitment to the integrity of the Indonesian nation and state which has a fatwa focusing on Pancasila, HTI and mass organizations. He is the chairman or imam of M3CB. Abstrak             Penelitian ini membahas tentang perjalanan hidup Abuya Muhtadi Banten yang merupakan salah satu kyai kharismatik asal Banten. Ajaran tentang keislaman warga Banten sangat eksis hal tersebut didasarkan pada sejarah lisan yang telah tersebar di kalangan masyarakat Indonesia. Selain itu dibuatnya tulisan ini guna untuk memberikan jawaban kepada orang-orang yang menafikan ajaran ulama yang telah dirangkum serta diimani. Penelitian ini bertujuan untuk mengetahui perjalanan hidup Abuya Muhtadi Banten. Penelitian ini diharapkan dapat menjawab pertanyaan mengenai sejarah kehidupan Abuya Muhtadi Banten. Penelitian ini menggunakan metode kualitatif. Dengan hasil penelitian yaitu Abuya Muhtadi merupakan anak pertama dari Abuya Dimyathi yang juga salah satu penerus dan juga pemegang pondok pesantren Raudhatul 'Ulum hingga saat ini. Abuya Muhtadi sejak kecil sudah diajarkan dan ikut serta mengikuti jejak ayahnya sebagai pendakwah yang diawali dengan kegiatan berguru dan mengaji yang dilakukan di pondok pesantren yang ada di Banten. Bekal pemahaman mengaji yang dimiliki oleh Abuya Muhtadi dijadikannya sebagai dasar untuk mendalami ilmu agama Islam. Abuya Muhtadi juga merupakan salah satu pengurus Mustayar PBNU. Abuya Muhtadi merupakan salah satu ulama yang memiliki komitmen terhadap keutuhan bangsa dan negara Indonesia yang memiliki fatwa berfokus pada Pancasila, HTI dan ormas. Ia merupakan ketua atau imam M3CB.